Kegagalan Konstruksi yang Tidak di Jamin Asuransi Ditinjau dari Teori Tanggung Jawab Hukum Perdata - Karnosaputra, Yanto; Murwadji, Tarsisius; Gultom, Elisatris (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 2 (2025), 2025)
The New The construction of the New Effluent Water Treatment Plant (EWTP) is a National Strategic Project aimed at managing crude oil industrial waste in accordance with prevailing regulations. However, the project failed at 98.84% completion due to a fire at the fuel tank prior to the handover phase. Legal issues subsequently arose, as the contractor neglected to renew the mandatory insurance coverage stipulated in the contract. This study aims to analyze the legal liability of the contractor for the uninsured project failure and to evaluate the legal consequences under Indonesia’s positive law, particularly Law No. 2 of 2017 on Construction Services and Law No. 1 of 2025 on State-Owned Enterprises (BUMN). The research employs a normative juridical approach, and the findings indicate that the contractor may be deemed in breach of contract (wanprestasi) under Article 1239 of the Indonesian Civil Code, leading to legal consequences including compensation for damages, delay penalties, and responsibility for project losses. The absence of insurance coverage invalidates any claim of force majeure and strengthens the contractor’s legal liability based on the pacta sunt servanda principle and risk management obligations within BUMN projects. This research underscores the critical importance of contractual compliance and risk mitigation through insurance protection as integral components in the execution of national infrastructure projects . Proyek pembangunan New Effluent Water Treatment Plant (EWTP) merupakan Proyek Strategis Nasional yang bertujuan mengelola limbah industri minyak mentah sesuai peraturan perundang-undangan. Namun, proyek mengalami kegagalan saat progres mencapai 98,84%, akibat kebakaran Tangki BBM sebelum serah terima. Permasalahan hukum pun muncul karena kontraktor lalai dalam memperpanjang jaminan asuransi yang secara kontraktual diwajibkan. Penelitian ini bertujuan untuk menganalisis bentuk tanggung jawab hukum kontraktor atas kegagalan proyek yang tidak diasuransikan serta mengevaluasi akibat hukumnya berdasarkan hukum positif Indonesia, khususnya UU No. 2 Tahun 2017 tentang Jasa Konstruksi dan UU No. 1 Tahun 2025 tentang BUMN. Metode yang digunakan adalah pendekatan yuridis-normatif dan hasil penelitian menunjukkan bahwa kontraktor dapat dikualifikasikan melakukan wanprestasi berdasarkan Pasal 1239 KUHPerdata, dengan konsekuensi hukum berupa kewajiban mengganti kerugian, membayar denda keterlambatan, serta tanggung jawab atas kerusakan proyek. Ketiadaan asuransi meniadakan pembelaan force majeure dan memperkuat tanggung jawab hukum kontraktor berdasarkan asas pacta sunt servanda serta prinsip pengelolaan risiko dalam proyek BUMN. Penelitian ini menegaskan pentingnya kepatuhan kontraktual dan manajemen risiko melalui perlindungan asuransi sebagai bagian integral dalam pelaksanaan proyek konstruksi nasional.